Influence of microwave irradiation on DNA hybridization and polymerase reactions. Issue 39 (26th September 2019) - Sun, Jinyu; Vanloon, Jesse; Yan, Hongbin
Graphical abstract: Highlights: DNA strand exchanges are affected by exposure to microwave irradiation. Polymerase-catalyzed reactions are affected by microwave. Temperature measurement by thermocouples enables real-time monitoring in reactions under microwave irradiation. Abstract: We report herein that exposure of DNA to microwave irradiation at constant temperature leads to faster strand exchange, as compared with same experiments carried out in a water bath at the same temperature. Furthermore, polymerase chain reactions carried out under microwave irradiation were faster than those in a water bath at the same temperature as well. While the causes of these differences are unclear at this time, this research suggests that microwave irradiation can lead to subtle changes in DNA structural dynamics and functions.